Phosphorylation of h1 Calponin by PKC epsilon may contribute to facilitate the contraction of uterine myometrium in mice during pregnancy and labor - Li Lesai; Zhang Yong; Zhou Changju (BMC, 2012)
Abstract Background The timely onset of powerful uterine contractions during parturition occurs through thick and thin filament interactions, similar to other smooth muscle tissues. Calponin is one of the thin filament proteins. Phosphorylation of calponin induced by PKC-epsilon can promote the contraction of vascular smooth muscle. While the mechanism by which calponin regulates the contraction of pregnant myometrium has rarely been explored. Here, we explore whether PKC-epsilon/h1 calponin pathway contribute to regulation of myometrial contractility and development of parturition. Methods We detected the expression of h1 calponin, phosphorylated h1 calponin, PKC-epsilon and phosphorylated PKC-epsilon in the different stages of mice during pregnancy and in labor by the method of western blot and recorded the contraction activity of myometrium strips at the 19th day during pregnancy with different treatments by the organ bath experiments. Results The level of the four proteins including h1 calponin, phosphorylated h1 calponin, PKC-epsilon and phosphorylated PKC-epsilon was significantly increased in pregnant mice myometrium as compared with that in nonpregnant mice. The ratios of phosphorylated h1 calponin/h1 calponin and phosphorylated PKC-epsilon/PKC-epsilon were reached the peak after the onset of labor in myometrium in the mice. After the treatment of more than 10(9-) mol/L Psi-RACK (PKC-epsilon activator), the contractility of myometrium strips from mice was reinforced and the level of phosphorylated h1 calponin increased at the same time which could be interrupted by the specific inhibitor of PKC-epsilon. Meanwhile, the change of the ratio of phosphorylated h1 calponin/h1 calponin was consistent with that of contraction force of mice myometrium strips. Conclusions These data suggest that in mice myometrium, phosphorylation of h1 calponin induced by the PKC-epsilon might facilitate the contraction of uterine in labor and regulate pregnant myometrial contractility.